Corporations and Counterinsurgency - Rosenau, William; Chalk, Peter; McPherson, Renny; Parker, Michelle; Long, Austin (RAND Corporation, 2023)
Multinational corporations can be significant actors in zones of violent conflict. Corporate actions to shape their environment can sometimes mitigate conflict, but as the authors show in their case studies, corporate activities can help generate and sustain violence.